Contact sensitization in children with atopic dermatitis - Ozceker, D.; Haslak, F.; Dilek, F.; Sipahi, S.; Yucel, E.; Guler, N.; Tamay, Z. (My University, 2019)
Background: Atopic dermatitis is a common illness in childhood. Children with atopic dermatitis are prone to develop cutaneous sensitization due to skin barrier dysfunction.